Activity to the scarlet macaw ara macao cyanoptera (PSITTACIFORMES: PSITTACIDAE) and habitat structure characteristics in marqués de Comillas, Chiapas - Mendoza-Cruz, Estefanía; Sánchez-Gutiérrez, Facundo; Valdez-Hernández, Juan Ignacio (Instituto de Ecología, A.C., 2017)
Ara macao cyanoptera is in the Red List of Threatened Species (IUCN, 2014), however research on its habitat is scarce. Structural characteristics of tree vegetation were studied in locations used by A. macao cyanoptera for nesting (An), feeding-resting (AyD), and sleeping (Do) in the Ejido Reforma Agraria, Marqués de Comillas, Chiapas. Focal trees were identified (AF) by hikes at morning and evening with the help of community guides. These AF were the center of 17 circular sampling units (UM) measuring 1000 m2: nine UM in locations An, six UM in locations AyD, and two UM in locations Do. Structural and diversity indices were calculated: importance value (IVI), forest value (IVF), Shannon-Wiener (H´) and floristic similarity. Forty six tree species, belonging to 44 genera and 22 families, were recorded; 15 species out of the total, belonging to 15 genera and nine families, were used by A. macao cyanoptera for nesting, feeding-resting, and sleeping. This species nested on Ceiba pentandra (IVI = 45.9, IVF = 45.6), Ficus cotinifolia (IVI = 30.2, IVF = 27.5) and Vatairea lundellii (IVI = 15.5, IVF = 12.1); during the non-reproductive season, A. macao cyanoptera slept on Acacia usumacintensis (IVI = 75.3, IVF = 124) and V. lundellii (IVI = 43.4, IVF = 49.7), while fruits and seeds from Spondias mombin (IVI = 22.1, IVF = 25.7) were 80% of its food. A. macao cyanoptera was found on silvo-pastures closed to fluvial zones which hold a floristic similarity between 29 and 75% with a density of 260 trees ha-1. Tree diversity (H´ = 3.1) is a support factor on the availability of food for this threatened bird species.